Design validity and reliability of test instruments for measuring football heading accuracy and coordination - Manshuralhudlori,; Iqbal Doewes, Rumi; Nuryadin, Islahuzzaman; Syaifullah, Rony (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
This study aimed to design, validate, and test the reliability of test instruments for measuring the accuracy and coordination of football headings. The research design employed a research and development approach based on the Gall and Borg developmental steps, which encompass needs analysis, product development, expert assessment, Group I test, Group II test, and the final product. A total of 100 male football players and 100 female football players participated in evaluating the design of the soccer heading skills test instrument. Three experts were invited to assess validity. Data analysis was performed using Aiken V to assess validity and Cronbach's alpha to assess reliability. The results indicated the following: (1) needs analysis, based on observation, found that football players' heading mastery was still low; (2) product design included numbered targets within the goal, comprising 10 points, the implementation of a header toss by the examiner during the heading test, and the specification of the heading zone; (3) the results of the validity test based on the expert's assessment showed an Aiken V value of 0.86 > 0.77 so that it was stated that the football heading test instrument was valid; (4) the test results for group I showed a reliability value of > 0.60 (0.878 for male players; 0.810 for female players) thus indicating consistency in the developed heading test instrument; (5) the test results for group II also showed a reliability value of > 0.60 (0.828 for male players; 0.802 for female players) thus indicating consistency in the developed heading test instrument; (6) the test results showed that the heading test instrument is valid and reliable so that the designed test becomes the final product. This heading test instrument can be used as a normative reference to measure the accuracy and coordination of football headings.